Autopilot Unmanned Smart Boat Vehicle (AUSV) Communication with LoRa RFM95 - Arfianto, Afif Zuhri; Rahmat, Mohammad Basuki; Dhiyavia, Fuad; Santoso, Tri Budi; Gunantara, Nyoman; Supriyanto, Eko; Ardhana, Valian Yoga Pudya (Society of Visual Informatics, 2020)
Autopilot is a system control application on moving vehicles such as airplanes, helicopters, or boat, which serves to stabilize the direction of motion in the desired time and the programmed path's direction. the autopilot control system is controlled by a series of microcontrollers and GPS that has the function to be able to determine and the desired object. This control system is designed with electrical system controls that utilize microcontrollers, sensor and GPS as control media. The development of autopilot prototypes is used for testing new control algorithms and the reliability of other electronic components such as sensors and microprocessors. A control system is needed to control the boat to its destination. The relatively accurate system dynamics model affects the steering performance of the autopilot system. The system in question can be considered a boat with an actuator rudder, which experiences external disturbances. this system is broadly divided into two parts: the control station part and the autonomous boat part. These two parts communicate with each other using LoRa device. The data sent from the control station to the autonomous boat is target latitude and longitude coordinates. The autonomous boat will send feedback in the form of boat latitude and longitude coordinates so that users can find out the current location of the boat. Autonomous Boat also provides feedback to the control station via LoRa in the form of boat coordinates so that users can find out the current location of the boat and whether the boat has reached the specified coordinates. The control station will send feedback from the boat to a database that can be monitored via the website to find out the boat's current condition on the website. Based on the results that have been obtained in the analysis and testing of the system. GPS sensor used in autonomous boat Ublox NEO-7m has an accuracy level with an average distance value of 3.220921 meters with the lowest cold start time of 7 seconds. Compass sensor used in autonomous boat CMPS11 has an accuracy level with an average value of 3.041667 degrees. Communication distance between autonomous boat and control station using LoRa with 5dBi antenna can reach 1406.79 meters in condition without obstruction between nodes. Data delivery system can be successfully sent from user to autonomout boat and sending feedback back to user. Delay update of boat coordinate data on interface has the lowest average of 30.8 seconds. Based on turning circle test results, autonomous boat is able to create imperfect circles with a radius of 8,364 m.